Subjugation, Dehumanization, and Resistance: - Sanjad Azvi; Ashik Istiak (Crossings)
In Antebellum America, both male and female slaves were oppressed and subjugated. However, the forms of these oppressions varied based on the gender of the slave, as did the ways in which different genders resisted their oppressors. This paper studies the differences and similarities in subjugation and resistance between male and female slaves in antebellum America, using the autobiographies of Frederick Douglass and Harriet Jacobs as primary sources. Douglass in his autobiography, Narrative of the Life of Frederick Douglass, an American Slave, describes how slave-owners used violence to ‘break’ male slaves' spirits and maintain their subservience, leading him to employ physical resistance against his masters and eventually flee to the North. On the other hand, Jacobs in her autobiography, Incidents in the Life of a Slave Girl illustrates how female slaves faced additional obstacles, such as fighting for their children's safety and living under the constant threat of sexual violence. These gendered differences reveal the complex ways in which power and oppression function in society, especially when analyzing them from an intersectional perspective. Through this analysis, the paper gains a deeper understanding of the nature of power dynamics connected to slavery.